2017
DOI: 10.2147/tcrm.s123148
|View full text |Cite
|
Sign up to set email alerts
|

<em>Helicobacter pylori</em> infection is not associated with failure to thrive: a case&ndash;control study

Abstract: PurposeThe long-term impact of Helicobacter pylori infection is complex, and concerns about the need for eradication exist. We conducted this case control study to investigate the association between H. pylori infection and failure to thrive (FTT).Patients and methodsFrom January 2009 to December 2011, 53 children with FTT group and matched children with the same sex and age and similar socioeconomic status without FTT (control group) were enrolled. A questionnaire was administered to the parents/guardian, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…Linear growth deficits were much more influenced compared to ponderal growth in H. pylori positive children [72]. In contrast, some studies indicated an absence of association between H. pylori infection and nutritional status of the infected children [74][75][76]. This is what we found as well in our study.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 69%
“…Linear growth deficits were much more influenced compared to ponderal growth in H. pylori positive children [72]. In contrast, some studies indicated an absence of association between H. pylori infection and nutritional status of the infected children [74][75][76]. This is what we found as well in our study.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 69%
“…The conclusions were inconsistent among these studies. Ten studies 24,26,29,30,35,38,40,42,44,51 believed that H . pylori infection had no or little impact on growth in children; however, most studies still supported that H .…”
Section: Resultsmentioning
confidence: 99%
“…48,49 The conclusions were inconsistent among these studies. Ten studies 24,26,29,30,35,38,40,42,44,51 believed that H. pylori infection had no or little impact on growth in children; however, most studies still supported that H. pylori infection was one environmental factor affecting children's growth. One study 31 suggested that H. pylori infection accompanied by iron deficiency anemia, rather than H. pylori infection alone, might delay pubertal growth.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…Following quality assessment of the remaining 16 observational studies, a total of 15 studies with a quality assessment score of ≥7 (Tables I-III) were included in the present study (Fig. 1), including two cohort (18,32), eight cross-sectional (20,21,(33)(34)(35)(36)(37)(38) and five case-control (39)(40)(41)(42)(43) studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, Dehghani et al (52) suggested that H. pylori infection did not affect the calculated standard deviation score (height and body mass index) (52). Cherian et al (35), Janjetic et al (38), Chiu et al (43) and Choe et al (33) reported that childhood growth and puberty are affected by iron deficiency anaemia and H. pylori infection, rather than H. pylori infection alone. Ortiz-Princz et al (46) revealed that early identification and intervention of H. pylori infection during childhood prevents further serious complications during adulthood, which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%